Ultrahigh damping and Young's modulus softening due to a/b twins in 10M Ni-Mn-Ga martensite. (15th March 2020) - Kustov, S.; Saren, A.; Sozinov, A.; Kaminskii, V.; Ullakko, K.
Abstract: We study Young's modulus and damping of 10M martensite in Ni50.0 Mn28.4 Ga21.6 magnetic shape memory alloy using a sample without a/c twin boundaries (TBs) and maximum or zero shear stress in a/b twinning planes. Damping is 300 times higher and modulus 3.5 times lower when shear stress acts on a/b TBs. Ultrahigh damping and low modulus are insensitive to magnetic field, show strong strain amplitude nonlinearity and are attributed to stress-induced motion of a regular system of mobile a/b TBs. Near the reverse transformation, E001 modulus without contribution of TBs is 10 times higher than reported previously for 10M polyvariant sample. Graphical abstract: Image, graphical abstract